The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1364/oe.21.023250
|View full text |Cite
|
Sign up to set email alerts
|

Top-hat beam output of a single-mode microstructured optical fiber: Impact of core index depression

Abstract: A new strategy to obtain a single-mode fiber with a flattened intensity profile distribution is presented. It is based on the use of an OVD-made high index ring deposited on a silica rod having a refractive index slightly lower than the silica used for the microstructured cladding. Using this strategy, we realized the first single-mode fiber with a quasi-perfect top-hat intensity profile around 1 µm. Numerical studies clearly demonstrate the advantage of using a core index depression to insure the single-mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 25 publications
4
25
0
Order By: Relevance
“…~50% larger than that of a regular LCF with the same core [6]. The flat-top mode in this work is the largest even demonstrated, with ~6 times the effective mode area of the record demonstrated previously [5]. A 6m-long fiber was tested in a laser configuration, showing a slope efficiency of ~84% at 1026 nm with respect to the absorbed pump power at 976 nm.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…~50% larger than that of a regular LCF with the same core [6]. The flat-top mode in this work is the largest even demonstrated, with ~6 times the effective mode area of the record demonstrated previously [5]. A 6m-long fiber was tested in a laser configuration, showing a slope efficiency of ~84% at 1026 nm with respect to the absorbed pump power at 976 nm.…”
Section: Introductionmentioning
confidence: 48%
“…Thus, a flat-top mode with a uniform intensity distribution is more suitable for larger effective mode-area. It has been shown that a flat-top mode can increase the effective mode area by ~60% without having to increase core size [3,4,5]. The flat-top mode is also of benefit in marking and material processing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Such electric field distribution could be useful for high power applications [12], [13]. We note that this mode electric field is not possible with real refractive index profile fibers, the exponential decay being more in the realm of slab dielectric waveguiding.…”
Section: Numerical Results and Discussionmentioning
confidence: 96%
“…1(d) shows the normalized electric field of FM at different wavelengths. It is interesting to note that at shorter wavelength, FM looks like a ring mode and with increasing wavelength the effective refractive index of mode decreases and it appears like a flat-top mode, thanks to the spreading electric field in the core region with increasing wavelength [5]. This flat-field leads to a very large effective area for the FM.…”
Section: Fiber Design and Working Principlementioning
confidence: 97%
“…It is interesting to see that due to the flat-top profile, it can also be used for several material processing applications such as welding, drilling, cutting, marking etc, where Gaussian beam profile is not good enough. PCF based designs with a flat-top output beam profile have been reported previously [5][6]. However, these designs are difficult to fabricate and reported area is lower than 2,000µm 2 .…”
Section: Fiber Design and Working Principlementioning
confidence: 99%